The Effect of Service Quality and Facilities on Inpatient Satisfaction at Malinau Regional General Hospital - Esra Pagewang; Entang Adhy Muhtar; Heri Wahyudi (Publikasi Indonesia, 2024)
This study aims to analyze how and to what extent the quality of service and facilities influence the satisfaction of inpatients at Malinau Hospital on the satisfaction of inpatients at Malinau Hospital, partially and simultaneously. The type of research used is a quantitative approach with a cross sectional study design with the aim of describing and analyzing whether there is a relationship between the independent variable and the dependent variable. The population in this study, the number of inpatient visits from June to October 2023 was 1,152, with a research sample of 92 respondents. Data collection techniques used questionnaires, interviews and documentation studies. The data analysis technique uses SPSS version 25. The results of the research obtained a multiple linear regression equation Y = 5.119 + 0.064 significant impact on the satisfaction of inpatients at Malinau District Hospital. The simultaneous test (F test) shows that the quality of services and facilities have a significant effect on the satisfaction of inpatients at Malinau Hospital simultaneously. The partial coefficient of determination (R2) shows that the variables (X1), (X2) are able to explain the variable (Y) by 55.0%. Meanwhile, the remaining 45.0% is explained by other variables not identified in this study.